2018
DOI: 10.1108/jedt-04-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

Factors confronting quantity surveying practice: the case of Nigeria

Abstract: Purpose As the challenges confronting a system are better addressed when known and understood, this paper aims to report the findings of a study that investigated the factors confronting professional quantity surveying using Nigeria as a case. Design/methodology/approach A questionnaire was developed and pre-tested as the instrument for collecting data. A total of 64 quantity surveyors practicing in Lagos, Port Harcourt and Enugu completed the questionnaire out of a non-probabilistic sample of 100. Severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Frei and Mbachu (2009) also stated that for QS to remain relevant in this world of continual change, urgent and far-reaching strategic transformation is required. Ogunsina et al (2018) listed numerous challenges confronting the Nigerian QS profession. Without scanning and discerning future directions and actively preparing for any impending changes, the QS profession stands at risk of receiving changes as threats rather than opportunities (Porth, 2003;Mbachu and Nkado, 2006).…”
Section: Mitigating Strategies Of Threats To Quantity Surveying Profession In the Nigerian Construction Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Frei and Mbachu (2009) also stated that for QS to remain relevant in this world of continual change, urgent and far-reaching strategic transformation is required. Ogunsina et al (2018) listed numerous challenges confronting the Nigerian QS profession. Without scanning and discerning future directions and actively preparing for any impending changes, the QS profession stands at risk of receiving changes as threats rather than opportunities (Porth, 2003;Mbachu and Nkado, 2006).…”
Section: Mitigating Strategies Of Threats To Quantity Surveying Profession In the Nigerian Construction Industrymentioning
confidence: 99%
“…Frei (2010) and Kadiri and Ayodele (2013) reported that the QS profession had been confronted with many challenges recently. Wao (2005) also stated that the profession had faced numerous challenges in its development compared to when it first came into existence Ogunsina et al (2018) assessed the factors confronting the practice of QS profession in Nigeria. Olatunji et al (2010) also revealed the fear of QS profession extinction in the face of technology.…”
Section: Previous Studiesmentioning
confidence: 99%
“…It is therefore crucial to ensure that performance quality is accurately measured and assessed. One way of updating a profession’s knowledge base is to ensure that the constituent skills, abilities and value of the profession are subjected to constant and continuous evaluation to critically highlight the important competencies (Dada and Jagboro, 2012; Wao, 2016; Ogunsina et al , 2018). In view of this, this study evaluates the currently exhibited and required competencies of quantity surveyors with a view to enhancing their quality of services, remaining in business and continuing to compete effectively and adequately.…”
Section: Introductionmentioning
confidence: 99%
“…QSFs can be likened to commercial organisations whose aim is to satisfy their customer through the delivery of quality services and thereby maximise profit. However, the recent study by Ogunsina et al (2018) gave the reminiscent of the prominent view and observation that QS profession is the least popular (Ajanlekoko, 2004) and the least valued and recognised within the Nigerian construction industry.…”
Section: Introductionmentioning
confidence: 99%